Chondral lesions in the hip: a review of relevant anatomy, imaging and treatment modalities. Issue 1 (16th April 2019) - Dallich, Alison A; Rath, Ehud; Atzmon, Ran; Radparvar, Joshua R; Fontana, Andrea; Sharfman, Zachary; Amar, Eyal
Abstract: The diagnosis and treatment of chondral lesions in the hip is an ongoing challenge in orthopedics. Chondral lesions are common and several classification systems exist to classify them based on severity, location, radiographic parameters, and potential treatment options. When working up a patient with a potential hip chondral lesion, a complete history, thorough physical exam, and ancillary imaging are necessary. The physical exam is performed with the patient in standing, supine, prone, and lateral positions. Plain film radiographs are indicated as the first line of imaging; however, magnetic resonance arthrogram is currently the gold standard modality for the diagnosis of chondral lesions outside of diagnostic arthroscopy. Multiple treatment modalities to address chondral lesions in the hip exist and new treatment modalities continue to be developed. Currently, chondroplasty, microfracture, cartilage transplants (osteochondral autograft transfer, mosaicplasty, Osteochondral allograft transplantation) and incorporation of orthobiologics (Autologous chondrocyte implantation, Autologous matrix-induced chondrogenesis, Mononuclear concentrate in platelet-rich plasma) are some techniques that have been successfully applied to address chondral pathology in the hip. Further refinement of these modalities and research in novel techniques continues to advance a surgeon's ability to address chondral lesions in the hip joint.